Implementation of the National Islamic Council Fatwa Number 47/DSN-MUI/II/2005 in Banks Syariah Mandiri Branch Manado - Faradila Hasan; Mar'atul Jannah S. Habu (IAIN Manado, 2019)
This study aims to determine the policies of Bank Syariah Mandiri Branch Manado in resolving murabahah receivables disputes for customers who are unable to pay and the realization of DSN No. fatwa. 47 / DSN-MUI / II / 2005 at Bank Syariah Mandiri, Branch Manado. The method used a qualitative research method using a normative approach. The informants interviewed were as many as five informants who were employees of the Bank Syariah Mandiri Branch of Manado. The concept of the settlement of murabahah receivables for customers who are unable to pay has two stages. First for customers who are categorized as having a reduced ability to pay but can still pay off the remaining debt by restructuring. The second stage is for customers who are classified as no longer able to pay their remaining debts even though the bank has provided several policies. Sharia Financial Institutions (LKS) may settle for customers who cannot complete or pay off their financing by agreed amounts and times; the system has been by the provisions of sharia in terms of the properties of the DSNI-MUI.